Immunomodulatory Effects of Saccharomyces cerevisiae Fermentation Product Supplementation on Immune Gene Expression and Lymphocyte Distribution in Immune Organs in Broilers - Chou, Wen K.; Park, Jungwoo; Carey, John B.; McIntyre, Don R.; Berghman, Luc R. (Frontiers in Veterinary Science, 2017)
A study was conducted to evaluate the molecular and cellular immunomodulatory effects of a Saccharomyces cerevisiae fermentation product (Original XPC, Diamond V) in broilers. Our lab has previously demonstrated that broilers fed XPC generate faster and stronger antigen-specific humoral immune responses to Newcastle Disease Virus (NDV) vaccination. This study aims at investigating the mechanism behind this increased immunocompetence. One-day-old broilers were randomly assigned to one of two treatments: 1.25 kg/ton Saccharomyces cerevisiae fermentation product (XPC treatment group) or control diet. Birds were vaccinated against NDV on d 1 (B1 strain) and d 21 (LaSota strain) post-hatch. Innate and adaptive immune-related gene expression profiles in central (thymus and bursa of Fabricius) and peripheral (spleen) immune organs were investigated at 14 and 28 days of age by qPCR array. Fold changes larger than 1.2 (P < 0.05) between treated and control were considered significant. Lymphocyte subpopulations in central and peripheral immune organs, and blood leukocytes were analyzed by flow cytometry at 14, 21, 28, and 42 days of age. In the spleen, Th1 immune responses and anti-viral genes, such as IFN-γ, and its downstream genes STAT4 and NFκB, were significantly up-regulated in the treated group by 14 days of age. In the thymus, genes belonging to different functional groups were influenced at different time points. Cytokine genes associated with lymphocyte maturation, differentiation, and proliferation, such as IL-1R, IL-2, and IL-15 were significantly up-regulated in the treated group by 28 days of age. Genes preferentially expressed in the medulla of the thymus and mature thymocytes, such as Myxovirus resistance gene 1, interferon regulatory factor-1 (IRF-1), IRF-7, and STAT1, were up-regulated in the birds supplemented with XPC. Birds supplemented with XPC had significantly higher percentages of CD3+, CD4+, and CD8+ T-cells in the thymus at day 28 of age, indicating production of more mature T-cells, which was consistent with gene expression results. Results suggest that XPC supplementation primes broilers to become more immunocompetent, without compromising growth performance.